Comparison of Dexmedetomidine 50μg versus 100μg added to 0.5% Levobupivacaine in Supraclavicular Brachial Plexus Block (BPB) for Arteriovenous Fistula (AVF) Surgery - Chong, Soon Eu; Ahmad, Mohd Nikman; Hassan, Mohd Fakhzan; Mohammad Zaini, Rhendra Hardy; Wan Hassan, Wan Mohd Nazaruddin (2013)
Background: Dexmedetomidine is an alpha-2 agonist used as sedation in ICU and remote anaesthesia. Unlike Clonidine, its effect as additive in peripheral nerve block has not been widely researched upon. The aim of this study is to compare the efficacy and outcome of additive dexmedetomidine 50μg versus 100μg to levobupivacaine 0.5% in supraclavicular brachial plexus block in AVF surgery . Methodology: Forty six adult with chronic renal failure patients scheduled for AVF surgery were studied in prospective, randomized, single operator double blinded study design. The supraclavicular block was performed with the ultrasound and a nerve stimulator technique.Group A (dexmedetomidine 50μg added to 20 ml of levobupivacaine 0.5 % + 1ml of normal saline) versus Group B (dexmedetomidine 100μg added to 20 ml of levobupivacaine 0.5 %). The onset, duration of action, haemodynamic parameters changes, vascular diameter changes and sedative effects were recorded Result: The onset of sensory and block is faster in Group B (8.08 ± 1.38); (P <0.002-sensory) and motor (11.33 ± 1.52; P< 0.024). Duration of action of the block is longer in Group B (12.3 ± 1.01); (P < 0.001). Sedation effects present in both group, however it is not statistically significant. (P> 0.5) Both group have a stable haemodynamic profiles. Group B causes significant increased the artery (0.020 ± 0.0067); (P<0.02) and vein diameter (0.022 ± 0.0074); (P<0.001). Conclusion: Dexmedetomidine as an additive for supraclacvicular block in ESRF patient for AVF surgery causes faster onset, prolonged duration of anesthesia, increase the artery and vein diameter and produced sedation effect with stable haemodynamic parameters.